The larvae of Rhyacophila rougemonti McLachlan 1880, Rhyacophila trifasciata Mosely 1930, Rhyacophila pallida Mosely 1930, and Rhyacophila tarda Giudicelli 1968 (Trichoptera: Rhyacophilidae), including a discriminatory matrix to the Rhyacophila larvae with tetrafilament abdominal gills from Italy and Corsica - Waringer, Johann; Malicky, Hans (Zootaxa, 2018)
This paper gives a description of the hitherto unknown or poorly known larvae of Rhyacophila rougemonti McLachlan 1880, R. trifasciata Mosely 1930, R. pallida Mosely 1930, and R. tarda Giudicelli 1968 (Trichoptera: Rhyacophilidae). Information on the morphology of the larvae is provided, and the most important diagnostic features are figured. This dataset is included in a discriminatory matrix of the Rhyacophila larvae with tetrafilament (i.e., four-filament) abdominal gills of Italy and Corsica described so far; only the species pair Rhyacophila pallida / R. tarda in Corsica remains unresolved. Larvae can be separated by the number of metathoracic gill filaments and anal proleg morphology, and by distribution patterns. Endemism is high in the species quartet described in the present paper: Rhyacophila pallida and R. trifasciata are Sardo-Corsican endemic species, R. tarda is restricted to Corsica, and R. rougemonti is a South-Apennine endemic species.